Diez, Jordi y O.P. Dwivedi (coords.) (2008), Global Environmental Challenges. Perspectives from the South, Toronto, Broadview Press, 274 p. - Ugalde, Vicente (Estudios Demográficos y Urbanos, 2010)
Diez, Jordi y O.P. Dwivedi (coords.). (2008). Global Environmental Challenges. Perspectives from the South, Toronto, Broadview Press.